PERENCANAAN PERLUASAN RUANG TUNGGU TERMINAL DOMESTIK BANDARA INTERNASIONAL AHMAD YANI SEMARANG - Fitra Guntari; Oka Fatra; Ambar Sugiyanto (Politeknik Penerbangan Indonesia Curug, 2017)
Ahmad Yani Airport Semarang has a wide Terminal Departing 5,907 m2 and the departure lounge of domestic 1230 m2 with 9% passengers increase every year. It is based on SKEP 347 / XII / 1999 on Standards for Design and / or Engineering of Airport Facilities and Equipment and Directives of Air Transportation No. KP 205 Year 2016 on Commercial Area Arrangement at Airport Passenger Terminal, and Regulation of the Minister of Transportation of the Republic of Indonesia No. PM 129 of 2015 on Guidelines for Level Service Agreement in Providing Services to Airport Users. The calculation results show the prediction of the number of passengers departing in 2021 as much as 2,658,258 people and the busy time passengers in 2021 were 1694 people. From the prediction of passengers in the next 5 years in the area can also the departure lounge of domestic 2733 m2 .